Lithium aluminosilicate glass ceramics
By adjusting the component ratio of lithium aluminosilicate glass ceramics, especially reducing the Li2O content and combining other oxides, the cost and performance problems caused by excessive lithium content are solved, and the low-cost, high thermal shock resistance and good melting performance of lithium aluminosilicate glass ceramics are achieved.
Patent Information
- Application Number
- CN202380081242.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-09
- Filing Date
- 2023-09-15
- Publication Date
- 2025-07-04
AI Technical Summary
Excessive lithium content in existing lithium aluminosilicate glass ceramics leads to an increase in cost and it is difficult to reduce the thermal expansion coefficient, affecting the melting performance and thermal shock resistance, and cannot compete with glass ceramics on the market.
By optimizing the component ratio, the Li2O content in the lithium aluminosilicate glass ceramic is reduced to 2.0-3.0 weight %, combined with SiO2 60-70%, Al2O3 17-25%, MgO 1.5-4.0% and ZnO 3.0-6.0%, the thermal expansion coefficient is controlled within the range of -0.5 to 1.9 ppm/K, and the thermal shock resistance and melting properties are improved.
The low-cost lithium aluminosilicate glass ceramic has a low thermal expansion coefficient in the range of 20°C to 700°C, ensuring compatibility with various heating elements and high thermal shock resistance, reducing processing temperature, and improving meltability and mechanical strength.
Smart Images

Figure BDA0005416721180000031 
Figure BDA0005416721180000131 
Figure BDA0005416721180000141
Abstract
Description
Technical Field
[0001] The present invention relates to a lithium aluminosilicate glass-ceramic suitable for use as a cooking surface of a cooking appliance and to its use. Background Art
[0002] Glass-ceramic cooking surfaces and the glass-ceramics used therefor have been known for many years. For this purpose, lithium aluminosilicate (LAS) glass-ceramics are used, which contain high quartz mixed crystals (HQMK) especially for transparent materials or hydrothermal quartz mixed crystals (KMK) especially for translucent or opaque materials as the main crystal phase. To manufacture such glass-ceramics, the raw glass, i.e. the so-called green glass, is first manufactured by conventional methods for glass manufacture. The green glass is converted into a glass-ceramic by a heat treatment process, i.e. ceramization.
[0003] The basic property of these materials used as cooking surfaces is that they have a very low thermal expansion in the temperature range from room temperature to 700 °C. The low thermal expansion in turn results in high thermal shock resistance. The thermal expansion is composed of a crystalline phase with negative thermal expansion and an amorphous residual glass phase with positive thermal expansion. In the glass-ceramics used to date, the lithium content is usually more than 3.6% to 5.0% by weight.
[0004] Due to the rising raw material price of lithium, it is economically advantageous to minimize the lithium content in the glass-ceramic. However, since lithium is one of the three main components in lithium aluminosilicate glass-ceramics, it cannot be reduced arbitrarily. The content of Li2O directly affects the key properties of the glass-ceramic, such as the viscosity important for manufacturability in the melt or the thermal expansion important for use as a cooking surface.
[0005] The price trend of lithium is not a new issue. The price of lithium has been rising continuously for the past 20 years. Nevertheless, due to the long-term demand, most of the glass-ceramics used for cooking surfaces on the market contain about 3.8% by weight of Li2O. So far, in practice, no glass-ceramic with a Li2O content of less than 3.5% and capable of competing with the glass-ceramics currently on the market has been found.
[0006] Glass-ceramics with a Li2O content of less than 3.5% by weight are known from the following documents: WO 2012 / 010341A1, EP3502069 A1, US2017050880, US2020189965, US2020140322, US2021387899, WO2021 / 224412A1. However, these glass-ceramics have various disadvantages, such as reduced thermal shock resistance or poor fusibility of the green glass.
[0007] Here, transparent glass ceramics are generally understood as glass ceramics with low light scattering. The transmittance of transparent glass ceramics can be adjusted within a wide range by absorption characteristics (i.e., colorability) components.
[0008] When transparent glass ceramics are used for cooking surfaces, they are either volume-colored by adding colored oxides or a bottom coating is provided to visually hide the technical devices located below the cooking surface. Various colored oxides can be used for the volume coloring of glass ceramics. These include in particular V2O5, CoO, Fe2O3, Cr2O3, Nd2O3, NiO, CuO, MnO, and MoO3. Each of these colored oxides has a different effect on the absorption of glass ceramics in the visible and infrared spectral ranges. The coloring of glass ceramics is described in particular in the following documents: WO 11089220 A1, US 8765619, DE 102008050263B4, DE 102009013127B4. Summary of the Invention
[0009] The object of the present invention is to provide a lithium aluminosilicate glass ceramic that has good green glass melting characteristics and is inexpensive without imposing restrictions on the use characteristics.
[0010] Good melting properties mainly include here: a processing point at a temperature below 1340 °C, preferably below 1330 °C, particularly preferably below 1320 °C. The processing point is the temperature at which the green glass has a viscosity of 10 4 dPa*s. The thermoforming of the green glass occurs near this temperature. The higher the temperature during thermoforming, the more complicated it is to remove the heat introduced into the forming machine by the glass. In the case of temperatures above 1340 °C, this can only be achieved by reducing the glass production rate to reduce the heat. However, this is economically disadvantageous.
[0011] During the thermoforming process, below the upper devitrification temperature, undesired spontaneous crystallization may occur. To prevent this, the upper devitrification temperature should be at least 15 K lower than the processing point, preferably at least 20 K, particularly preferably at least 30 K.
[0012] In particular, the glass ceramic should meet all the requirements for use in combination with all types of heating elements as a cooking surface. These heating elements include in particular radiant heating elements, induction heating elements, and gas heating elements. This particularly requires a sufficiently high thermal shock resistance and high long-term temperature resistance characteristics.
[0013] The object of the present invention is achieved by the subject matter of the independent claims. Preferred embodiments and improvements are derived from the dependent claims.
[0014] The lithium aluminosilicate glass-ceramic according to the invention has a coefficient of thermal expansion in the range from 20 °C to 700 °C of -0.5 to 1.9 ppm / K. The glass-ceramic contains the following components in % by weight, based on oxides, in the indicated amounts:
[0015]
[0016]
[0017] The glass-ceramic with the corresponding coefficient of thermal expansion has both high thermal shock resistance and high long-term thermal stability. Thereby it is suitable as a cooking surface for use with all types of heating elements. The coefficient of expansion is at least -0.5 ppm / K. Here, "ppm" means "parts per million", i.e., the relative change in dimension for a temperature change of 1 K is 10 -6 . A more negative coefficient of thermal expansion is to be avoided. In the case of negative expansion, i.e., shrinkage, tensile stresses are generated in the surface of the glass-ceramic during heating. When the value is less than -0.5 ppm / K, the stress reduces the mechanical strength of the cooking surface at the typical operating temperatures of the cooking appliance. A coefficient of thermal expansion above 1.9 ppm / K is also to be avoided. When the expansion exceeds 1.9 ppm / K, a sufficiently high thermal shock resistance cannot be ensured, so that the glass-ceramic cannot be used in cooking appliances with radiant heating elements.
[0018] In a further embodiment of the invention, the coefficient of thermal expansion is at least -0.4 ppm / K, -0.2 ppm / K, 0.0 ppm / K, 0.2 ppm / K, 0.4 ppm / K, 0.6 ppm / K, 0.8 ppm / K, or even 0.9 ppm / K. In addition, the coefficient of thermal expansion is preferably at most 1.7 ppm / K, 1.5 ppm / K, 1.3 ppm / K, 1.1 ppm / K, 1.0 ppm / K, 0.8 ppm / K, or even at most only 0.6 ppm / K.
[0019] In a preferred embodiment of the invention, the coefficient of thermal expansion of the glass-ceramic is -0.5 to 1.0 ppm / K, preferably -0.1 to 0.8 ppm / K, particularly preferably 0 to 0.6 ppm / K. This glass-ceramic is particularly suitable for the cooking surface of cooking appliances with radiant heating elements.
[0020] In a further preferred embodiment of the invention, the coefficient of thermal expansion of the glass-ceramic is 0.5 to 1.9 ppm / K, preferably -0.7 to 1.7 ppm / K, particularly preferably 0.9 to 1.5 ppm / K. This glass-ceramic is suitable for use, for example, as the cooking surface in cooking appliances with induction heating elements.
[0021] The glass-ceramic according to the invention contains the following components in % by weight:
[0022] SiO2 60 - 70,
[0023] Al2O3 17 - 25, and
[0024] Li2O 2.0 - 3.0.
[0025] The components SiO2 and Al2O3 together with Li2O form the main components of the crystalline phase in the glass - ceramic. At the same time, they essentially determine the glass - forming properties and the viscosity of the green glass.
[0026] The SiO2 content of the glass - ceramic according to the invention should be at most 70 wt%, because this component greatly increases the viscosity of the glass, especially the processing point. For good glass melting and low forming temperature,
[0027] a higher SiO2 content is uneconomical. The minimum SiO2 content should be 60 wt%, because this is beneficial for the required properties such as chemical resistance and temperature resistance. When the SiO2 fraction is very high, exceeding 70 wt%, deep - seated quartz crystals are formed during the ceramization process. This leads to a sharp increase in thermal expansion.
[0028] Preferably, the glass - ceramic contains at least 61 wt%, 62 wt%, 63 wt%, 64 wt%, or even 65 wt% of SiO2. The more SiO2 the glass - ceramic contains, the better its temperature resistance and chemical resistance. In addition, it preferably contains at most 69 wt%, 68 wt%, 67 wt%, or even only 66 wt% of SiO2. The less SiO2 the glass - ceramic contains, the better the fusibility and processability of the green glass in hot forming.
[0029] The Al2O3 content of the glass - ceramic according to the invention is in the range of 17 to 25 weight - percent. A higher Al2O3 fraction leads to devitrification problems and the formation of unwanted mullite. Therefore, it should not exceed 25 wt%. An Al2O3 content below 17 wt% is not conducive to the formation of high - quartz mixed crystals and promotes the formation of unwanted crystalline phases.
[0030] Preferably, the glass - ceramic contains at least 18 wt%, 19 wt%, or even 20 wt% of Al2O3. The more Al2O3 the glass - ceramic contains, the better its temperature resistance. In addition, it preferably contains at most 24 wt%, 23 wt%, 22 wt%, or even only 21 wt% of Al2O3. The less Al2O3 the glass - ceramic contains, the better the fusibility and processability of the green glass in hot forming.
[0031] It has been shown that if the glass - ceramic contains 17 - <19.0 wt%, preferably 17.5 - 18.9 wt%, particularly preferably 18 - 18.8 wt% of Al2O3, it is particularly advantageous for the fusibility of the green glass.
[0032] It has been proven that if the glass-ceramic contains > 21.0 - 25 wt%, preferably 21.5 - 24 wt%, particularly preferably 22.0 - 23 wt% of Al2O3, it is particularly advantageous for the heat resistance of the glass-ceramic.
[0033] The Li2O content of the glass-ceramic according to the invention is in the range of 2.0 - 3.0 wt%. Surprisingly, it has been proven that when the Li2O content is within this range in combination with the remaining components within the above ranges, a glass-ceramic with high thermal shock resistance and good fusibility can be achieved. Since Li2O has a great influence on the thermal expansion of the glass-ceramic, Li2O is selected within the above range to be combined with the remaining components of the glass-ceramic of the invention in order to achieve the thermal shock resistance required by the invention. Additionally, a Li2O fraction of more than 2.0 wt% has a positive effect on the manufacturability of the glass-ceramic, because this reduces the electrical resistance of the glass melt, reduces the viscosity, and thus also reduces the processing point. By reducing the viscosity of the glass melt, the clarification efficiency can also be increased. Improved clarification results in fewer production rejects due to the formation of bubbles in the green glass.
[0034] In a preferred embodiment, the glass-ceramic contains at least 2.1 wt%, 2.2 wt%, 2.3 wt%, or even 2.4 wt% of Li2O. As the upper limit, preferably, the glass-ceramic contains at most 2.9 wt%, 2.8 wt%, 2.7 wt%, or even 2.6 wt% of Li2O. Particularly preferably, the glass-ceramic contains 2.1 - 2.9 wt%, or 2.2 - 2.8 wt%, or 2.3 - 2.7 wt% or even 2.4 - 2.6 wt% of Li2O. Glass-ceramics with particularly high thermal shock resistance can be obtained within these narrower limits.
[0035] For cost reasons, natural mineral raw materials (such as spodumene or petalite) or alternatively synthetically produced Li2CO3 are usually used as the source of lithium. However, natural mineral raw materials contain impurities that may, for example, have an undesirable effect on the optical properties of the glass-ceramic. In addition, the amount of impurities in the natural raw materials may vary with each delivery, which makes it difficult to adjust the required properties of the glass-ceramic. For this reason, it is also advantageous to minimize the amount of Li2O in the glass-ceramic.
[0036] In a preferred embodiment, the glass-ceramic contains high quartz mixed crystals as the main crystal phase. The "main crystal phase" means that the volume fraction of the high quartz mixed crystals contained in the glass-ceramic is greater than the volume fraction of the hydrothermal quartz mixed crystals. In a further embodiment of this embodiment, the glass-ceramic contains <10 vol%, preferably <5 vol%, particularly preferably <3 vol% of hydrothermal quartz mixed crystals. Here, vol% refers to the volume of the glass-ceramic, preferably the volume of the crystal phase. The volume fraction is determined from the X-ray diffraction spectrum using Rietveld analysis.
[0037] Hydrothermal quartz mixed crystals generally have a higher thermal expansion than high quartz mixed crystals. Therefore, the coexistence of a high fraction of high quartz mixed crystals and a low fraction of hydrothermal quartz mixed crystals is particularly advantageous for the thermal expansion coefficient of the glass-ceramic. It thus improves the thermal shock resistance of the glass-ceramic.
[0038] In addition to the above amounts of SiO2, Al2O3 and Li2O, the glass-ceramic according to the invention further contains >1.5 - 4.0 wt% of MgO. Since MgO causes an increase in the thermal expansion of the glass-ceramic, the amount of MgO in the glass-ceramic is limited to a maximum of 4.0 wt%. Preferably, the glass-ceramic contains a maximum of 3.6 wt%, 3.3 wt%, 3.0 wt%, 2.6 wt%, or even only 2.3 wt% of MgO.
[0039] MgO is used to lower the processing point and the upper devitrification temperature. The glass-ceramic preferably may contain at least 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, or even 2.0 wt% of MgO.
[0040] In a preferred further development of the invention, the glass-ceramic contains 1.6 - 3.6 wt%, 1.7 - 3.3 wt%, 1.8 - 3.0 wt%, 1.9 - 2.6 wt% or even 2.0 - 2.3 wt% of MgO.
[0041] In addition, the glass-ceramic according to the invention contains >3.0 - 6.0 wt% of ZnO. ZnO causes the formation of undesirable zinc spinel crystals, especially in combination with a large amount of Al2O3. Therefore, the amount in the glass-ceramic according to the invention is limited to 6.0 wt%. Additionally, experience has shown that glass-ceramics with very high amounts of ZnO tend to form undesirable crystals on the surface of the glass-ceramic. Therefore, the amount of ZnO is preferably limited to a maximum of 5.6 wt%, 5.3 wt%, 5.0 wt%, 4.6 wt% or even 4.3 wt%.
[0042] In the glass-ceramics according to the invention, ZnO reduces the processing point and the upper devitrification temperature. Therefore, the glass-ceramics preferably contain at least 3.1 wt%, 3.2 wt%, 3.3 wt%, 3.4 wt%, or even 3.5 wt% of ZnO. In these ranges, the thermal shock resistance of the glass-ceramics is particularly improved.
[0043] In a preferred embodiment, for the above reasons, the glass-ceramics contain 3.1 - 5.6 wt%, 3.2 - 5.3 wt%, 3.3 - 5.0 wt%, 3.4 - 4.7 wt%, or even 3.5 - 4.3 wt% of ZnO.
[0044] The addition of Na2O and K2O improves the fusibility and devitrification characteristics during the forming of the glass. These two components can increase the electrical conductivity of the melt. This is beneficial for the coupling-in of the heat introduced by the heating device into the melting bath. However, since these components do not incorporate into the crystal phase but remain essentially in the residual glass phase of the glass-ceramics, their contents are limited. Excessive contents impair the crystallization characteristics when the starting glass that can be crystallized transforms into glass-ceramics. This is especially the rapid ceramization rate. In addition, higher contents act unfavorably on the time / temperature tolerance of the glass-ceramics.
[0045] In a further development of the invention, for the above reasons, the glass-ceramics contain 0 - 0.5 wt% or 0.05 - 0.4 wt% or even 0.1 - 0.3 wt% of Na2O.
[0046] In a further additional development of the invention, for the above reasons, the glass-ceramics contain 0 - 0.5 wt% or 0.05 - 0.4 wt% or even 0.1 - 0.3 wt% of K2O.
[0047] The sum of the alkalis Na2O + K2O in combination with the remaining components of the glass-ceramics is preferably at least 0.2 wt% and at most 1 wt%, preferably at least 0.3 wt%, 0.4 wt%, or even 0.5 wt%, and at most 1.0 wt%, 0.9 wt%, 0.8 wt%, 0.7 wt%, or even 0.6 wt%. In these amounts, a particularly good compromise between fusibility and devitrification is achieved for the glass-ceramics according to the invention without the ceramization rate becoming worse.
[0048] The fusibility and thermal expansion can be finely adjusted via the ratio of K2O to Na2O. Na2O improves melting and reduces the viscosity of the glass melt more strongly than K2O in the current composition, but also increases the thermal expansion of the glass-ceramics more strongly.
[0049] In a first advantageous embodiment of the present invention, the ratio of K2O to Na2O is in the range of 0.1 - 2, preferably 0.5 - 1.5, particularly preferably 0.7 - 1.3. In this range, the above-mentioned properties are particularly compromised.
[0050] In a second advantageous embodiment of the present invention, the ratio of K2O to Na2O is in the range of 0.1 - <1, preferably 0.2 - 0.9, particularly preferably 0.3 - 0.8. This embodiment has improved fusibility and viscosity. This can be particularly advantageous when the remaining components contained in the glass-ceramic tend to be more refractory or have a higher viscosity.
[0051] In a third advantageous embodiment of the present invention, the ratio of K2O to Na2O is in the range of 1 - 2, preferably 1.1 - 1.9, particularly preferably 1.2 - 1.8. This embodiment has improved thermal expansion. This can be particularly advantageous when the remaining components contained in the glass-ceramic tend to have a higher thermal expansion.
[0052] Furthermore, the glass-ceramic according to the present invention contains 0.1 - <1.0 wt% of SnO2. Starting from 0.1 wt%, the combination of SnO2 with the other components of the glass-ceramic according to the present invention helps to ensure improved nucleation. The amount of SnO2 should not exceed <1.0 wt%. Higher contents lead to the precipitation of Sn-containing crystalline phases at the contact material (e.g., Pt / Rh) during shaping and should be avoided. Preferably, the glass-ceramic contains 0.1 - <1.0 wt% of SnO2, preferably 0.15 - 0.8 wt%, particularly preferably 0.2 - 0.6 wt% of SnO2.
[0053] In a further embodiment of the present invention, the glass-ceramic may contain 0.1 - 0.8 wt%, preferably 0.2 - 0.7, particularly preferably 0.3 - 0.6 wt% of SnO2. SnO2 in these amounts can support the clarification of green glass. The glass-ceramic with these amounts of SnO2 is characterized by particularly few defects caused by trapped air bubbles.
[0054] In another improved embodiment of the present invention, the glass-ceramic may contain 0 - 0.8 wt%, preferably 0.1 - 0.6 wt%, particularly preferably 0.2 - 0.4 wt% of CeO2. The combination of CeO2 with SnO2 can also support clarification and improve the bubble quality.
[0055] In a preferred further development of the invention, the glass-ceramic contains 1.0 - 5.0 wt% of TiO₂. TiO₂ contributes in particular, together with SnO₂, to nucleation. The amount of TiO₂ is limited to a maximum of 5.0 wt%. Larger amounts of TiO₂ would lead to devitrification during thermoforming. Additionally, it would lead to an undesired increase in the refractive index of the residual glass phase. Preferably, the glass-ceramic contains at least 1 wt%, 1.5 wt%, 2.0 wt%, >2.5 wt% or even >3.0 wt% of TiO₂. At the same time, it preferably contains a maximum of 4.5 wt%, 4.2 wt%, 4.0 wt%, 3.8 wt%, 3.6 wt% or even only 3.4 wt% of TiO₂. In the case of a higher TiO₂ fraction, nucleation proceeds faster. Thereby, the ceramization time of the glass-ceramic can be reduced. A lower TiO₂ fraction can stabilize the ceramization process and prevent accidental devitrification of the green glass during thermoforming.
[0056] In a preferred embodiment, for the reasons mentioned above, the glass-ceramic contains, for example, 1.0 - 5.0 wt%, preferably 2 - 4.5 wt%, particularly preferably >2.5 - 4.0 wt% of TiO₂.
[0057] In the production of glass-ceramics, As₂O₃ and Sb₂O₃ are generally used as clarifying agents. However, in the glass-ceramics according to the invention, these components have surprisingly proven to be disadvantageous for devitrification stability. Therefore, the amounts of As₂O₃ and Sb₂O₃ are preferably each limited to less than 0.1 wt%. Particularly preferably, the glass-ceramic contains less than 0.09 wt%, 0.08 wt%, 0.07 wt%, 0.06 wt% or even less than 0.05 wt% of As₂O₃ and Sb₂O₃, respectively. Particularly preferably, the glass-ceramic does not contain As₂O₃ and Sb₂O₃ except for unavoidable traces.
[0058] However, As₂O₃ and Sb₂O₃ can occur as impurities in the glass-ceramic, especially when using batches containing As₂O₃ and Sb₂O₃ for manufacturing the glass-ceramic. This is especially the case when using batches from the recycling loop for cooking surfaces. For reasons of environmental protection and sustainability, it is advantageous to use batches from the recycling loop as raw materials. Therefore, the glass-ceramic preferably contains at least 0.01 wt%, 0.02 wt%, 0.03 wt% or even at least 0.04 wt% of As₂O₃ and / or Sb₂O₃, respectively. If both As₂O₃ and Sb₂O₃ are present, they are each present in the said amounts.
[0059] However, As2O3 and Sb2O3 can contribute to the clarification of the green glass and thus improve the bubble quality. For this purpose, in a further development of the present invention, the glass-ceramic contains 0.1 - 1.8 wt%, 0.2 - 1.7 wt%, 0.3 - 1.6 wt%, or even 0.4 - 1.5 wt% of As2O3. Alternatively, the glass-ceramic contains 0.5 - 2.1 wt%, 0.6 - 2.0 wt%, 0.7 - 1.9 wt%, 0.8 - 1.8 wt%, 0.9 - 1.7 wt%, or even 1.0 - 1.6 wt% of As2O3.
[0060] Furthermore, in a further development of the present invention, the glass-ceramic contains 1.0 - 4.0 wt% of ZrO2. ZrO2 acts mainly as a nucleating agent in the glass-ceramic. A content of 1.0 wt% of ZrO2 and especially in combination with the above amounts of SnO2 and TiO2 is advantageous for improving nucleation.
[0061] The amount of ZrO2 is preferably limited to a value of 4 wt% because ZrO2 increases the viscosity of the glass melt and thus also the processing point. Additionally, ZrO2 can lead to devitrification during the thermoforming process. Here, this can lead to the formation of undesired baddeleyite. Preferably, the glass-ceramic contains at least 1.3 wt%, particularly preferably 1.7 wt% of ZrO2. Furthermore, it preferably contains at most 3.9 wt%, 3.8 wt%, 3.2 wt%, 3.0 wt%, or even only 2.0 wt% of ZrO2. With these amounts, a particularly good compromise can be achieved between the positive contribution to nucleation and an acceptable deterioration of fusibility and thermoforming.
[0062] In a further development of the present invention, for the above reasons, the glass-ceramic contains 1.0 - 4.0 wt%, preferably > 1.3 - 3.9 wt%, particularly preferably > 1.7 - 3.8 wt% of ZrO2.
[0063] In a further development of the present invention, the glass-ceramic contains 1.0 - 4.0 wt% of BaO. BaO, like Li2O, reduces the viscosity of the glass melt and thus the processing point. To improve the fusibility of the green glass, it is advantageous that the glass-ceramic contains at least 1.0 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, or even 1.8 wt% of BaO when combined with the amount of Li2O according to the present invention. In the glass-ceramic, BaO also makes a significant contribution to improving the devitrification characteristics during the thermoforming of the green glass.
[0064] However, it has been shown that BaO negatively affects the formation of the crystalline phase during ceramization. In order to avoid the need for a long ceramization time, the amount of BaO is therefore preferably limited to a maximum of 4.0 wt%, 3.6 wt%, 3.3 wt%, 3.0 wt%, or even 2.7 wt%. The less BaO the glass-ceramic contains, the faster the ceramization proceeds.
[0065] In a further development of the invention, the glass-ceramic contains 1.0 - 4.0 wt%, or 1.2 - 3.6 wt%, or 1.4 - 3.3 wt%, or even 1.6 - 3.0 wt% of BaO.
[0066] In a further additional development of the invention, the glass-ceramic contains more BaO than Li2O. This acts positively on the reduction of the viscosity of the glass melt and the devitrification resistance of the green glass.
[0067] The addition of the alkaline earths CaO and SrO as well as B2O3 improves the fusibility and devitrification properties during the shaping of the glass. CaO can in particular be contained in the glass-ceramic to lower the processing point and the upper devitrification temperature. However, since these components do not incorporate into the crystalline phase but remain essentially in the residual glass phase of the glass-ceramic, the content is limited. Excessive content impairs the crystallization properties when the starting glass that can be crystallized is converted into the glass-ceramic, in particular the rapid ceramization rate. In addition, a higher content acts unfavorably on the time / temperature tolerance of the glass-ceramic. Therefore, the glass-ceramic contains each of these components in an amount of 0 - 2 wt%.
[0068] In a further development of the invention, the glass-ceramic can contain 0 - <1 wt% of P2O5. P2O5 acts positively on the devitrification stability of the green glass. However, a larger amount will reduce the ceramization rate and act negatively on the acid resistance of the glass-ceramic. Therefore, preferably the amount of P2O5 can even be limited to a maximum of <1 wt%, preferably a maximum of 0.9 wt%, particularly preferably a maximum of 0.8 wt%. In order to improve the devitrification stability, it is advantageous for the glass-ceramic to contain at least 0.01 wt%, preferably at least 0.05 wt%, particularly preferably at least 0.1 wt% of P2O5.
[0069] In a further embodiment of the invention, it may be advantageous for the glass-ceramic to contain Cl - . Already, the addition of a certain amount of Cl - results in better bubble quality of the green glass and thus better bubble quality of the glass-ceramic. It has been demonstrated by combination with the remaining components that the glass-ceramic contains 0.003 - 0.1 wt%, preferably 0.005 - 0.03 wt%, particularly preferably 0.007 - 0.02 wt% of Cl -Particularly advantageous. Amounts below 30 ppm do not have a sufficient impact on the bubble quality. Amounts above 1000 ppm should be avoided because the added chloride fraction may react with other components in the mixture and with the process exhaust gases. Here, for example, HCl may be formed, which can cause corrosive damage to the bath. In addition, the evaporation of alkali metal chlorides and alkaline earth metal chlorides is also undesirable. The amount of Cl in the glass-ceramic can be adjusted, for example, by adding NaCl to the mixture. - amount.
[0070] In addition to these components, in a further embodiment of the invention, the glass-ceramic can also contain coloring components. As coloring components, for example, V2O5, CoO, Fe2O3, Cr2O3, Nd2O3, NiO, CuO, MnO or MoO3 can be included singly or in combination. The specific choice of the type and amount of the coloring component depends on the optical properties to be achieved.
[0071] The coloring of the glass-ceramic is a complex, non-linear process. Many of the components contained in the glass-ceramic can affect the degree to which the coloring component absorbs light. Therefore, a person skilled in the art will adjust the amount of the coloring component according to the respective basic composition of the glass-ceramic to obtain the desired optical properties.
[0072] The coloring of the glass-ceramic according to the invention by means of V2O5 as the main coloring agent is shown here, for example, as follows. To reduce the transmittance to the desired value, more V2O5 will be used compared to a comparable glass-ceramic with a higher Li2O fraction. Thus, the reduction of Li2O weakens the absorption of V2O5 in the glass-ceramic. Similar, sometimes even opposite correlations also exist with the other components of the basic composition.
[0073] Even small amounts of V2O5 usually enable very intense coloring in the glass-ceramic. The glass-ceramic colored with V2O5 has a relatively low transmittance in the blue and green spectral ranges, while having a relatively high transmittance in the red spectral range. The glass-ceramic preferably contains 0 to 0.1 wt% of V2O5. Particularly preferably, it contains >0.002 to 0.08 wt%, >0.003 to 0.07 wt%, >0.004 to 0.06 wt%, >0.005 to 0.05 wt%, or even >0.01 - 0.04 wt% of V2O5. With these amounts of V2O5, for a thickness of 4 mm, the light transmittance of the glass-ceramic can be adjusted in the range of 0.1% to 80%.
[0074] In a particularly preferred further embodiment of the above-described embodiments, the ratio V2O5 / Li2O is 0.005 - 0.06, preferably 0.007 - 0.055, and particularly preferably 0.01 - 0.05. Without any limitation in generality, it is assumed that the coloring effect of V2O5 depends on the microstructure of the glass-ceramic. The glass-ceramic according to the invention has a relatively low crystalline phase fraction due to the low Li2O content, and at the same time has a small grain size. It has been shown that when the ratio of V2O5 to Li2O is adjusted within the above range, particularly effective coloring can be achieved. When this ratio is set within this range, for a thickness of 4 mm, the spectral transmittance at a wavelength of 630 nm can reach within the range of 0.5 - 15%, preferably within the range of 1 - 13%, and particularly preferably within the range of 2 - 10%. In the case of these transmittances, when using the glass-ceramic as a cooking surface, commercially available red light-emitting displays can be applied.
[0075] With the help of MoO3, the glass-ceramic can be colored particularly neutrally. The advantage of this is that light-emitting displays with a white light color can be applied in cooking appliances without changing the color of the light of the display when passing through the glass-ceramic. The glass-ceramic preferably contains 0 to 0.5 wt% of MoO3. Particularly preferably, it contains >0.002 to 0.4 wt%, >0.003 to 0.3 wt%, >0.004 to 0.2 wt%, >0.005 to 0.15 wt%, or even >0.01 to 0.1 wt% of MoO3. With these amounts of MoO3, for a thickness of 4 mm, the light transmittance of the glass-ceramic can be adjusted within the range of 0.1% to 80%. At the same time, a white light-emitting display can achieve a colorless-distortion presentation.
[0076] In a particularly preferred further embodiment of the above-described embodiments, the ratio MoO3 / Li2O is 0.015 - 0.1, preferably 0.02 - 0.08, and particularly preferably 0.025 - 0.07. By setting this ratio within this range, for a thickness of 4 mm, a light transmittance within the range of 0.5 - 4%, preferably 0.8 - 3.5%, particularly preferably 0.7 - 3.3%, and more particularly preferably 1.0 - 3.0% can be achieved. With these transmittances, when using the glass-ceramic as a cooking surface, a white light-emitting display can be used. At the same time, the visibility of the components present inside the cooking appliance is also greatly reduced.
[0077] Nd2O3 can also be used for coloring. It differs from the other colorants in that it produces relatively narrow absorption bands in the glass-ceramic. These absorption bands are mainly located in the green spectral range. With a small amount of Nd2O3, the color coordinates of the transmitted light through the glass-ceramic can be finely adjusted. For example, glass-ceramics containing only a small amount of Fe2O3 as a coloring component usually have a yellowish tint. This can occur, for example, when the glass-ceramic contains both TiO2 and Fe2O3 introduced through raw material impurities. If such a glass-ceramic has, for example, a white bottom coating, these bottom coatings have a clearly perceptible yellowish tint. In such glass-ceramics, the addition of Nd2O3 can be used to reduce or eliminate the yellowish tint without significantly reducing the light transmittance. This makes it possible to produce cooking surfaces with a white appearance.
[0078] Preferably, the glass-ceramic contains Nd2O3 in an amount of 0 - 0.6 wt%. Since Nd2O3 is relatively expensive, its amount should be limited to 0.6 wt%. Particularly preferably, the glass-ceramic contains 0.005 - 0.5 wt%, 0.01 - 0.4 wt%, 0.02 - 0.3 wt%, 0.03 - 0.2 wt%, or even 0.04 - 0.1 wt% of Nd2O3.
[0079] Fe2O3 affects not only the transmittance in the visible spectral range but also the transmittance of near-infrared light with wavelengths up to about 3 μm. Therefore, Fe2O3 not only affects the achievability of a specific color or the presentability of a color display. The absorption of near-infrared light determines how much heat energy the glass melt in the trough can absorb. This determines how much of the heating power of the radiant heating element can pass through the glass-ceramic. This also determines whether and which infrared sensors can be used in the stove. For example, these sensors can be designed as optical touch sensors or infrared receivers for wireless data transmission. At the same time, Fe2O3 is often contained as an impurity in the raw materials used for production. A higher content of Fe2O3 in the glass-ceramic makes it possible to use raw materials with a higher impurity content but lower cost. All of these must be considered when selecting the appropriate amount of Fe2O3. The amount of Fe2O3 should preferably be 0 - 0.4 wt%. Glass-ceramics containing more than 0.4 wt% of Fe2O3 are not compatible with commercially available radiant heating elements for cooking appliances due to the low transmittance of near-infrared light. Preferably, the glass-ceramic contains 0.005 - 0.3 wt%, 0.01 - 0.25 wt%, 0.02 - 0.2 wt%, or even 0.04 - 0.18 wt% of Fe2O3. Such glass-ceramics can be produced at low cost and are at the same time compatible with radiant heating elements and optical sensors for cooking appliances. Fe2O3 is usually contained as an impurity in the raw materials used for glass production, such as spodumene.
[0080] CoO can be included in the glass-ceramic, for example, in an amount of 0 - 0.5% by weight. Preferably, it is included in an amount of 0.01 - 0.2% by weight, more preferably 0.02 - 0.08% by weight, and particularly preferably 0.04 - 0.06% by weight.
[0081] Preferably, the glass-ceramic colored with 0.02 - 0.1% by weight of CoO additionally contains 0.02 - 0.1% by weight of Cr2O3. The glass-ceramic particularly preferably further contains 0.05 - 0.25% by weight of Fe2O3 and especially <30 ppm of V2O5. With these amounts of CoO and preferably other colorants, for a thickness of 4 mm, the light transmittance of the glass-ceramic can be adjusted within the range of 0.1% to 80%. Thus, a white display can also be achieved within the warm white spectral range.
[0082] Different from V2O5, MoO3 or CoO, Cr2O3, NiO, CuO and MnO are usually used for auxiliary coloring, but they are rarely used as main colorants. Here, the main colorant refers to the coloring component that has the most important influence on the transmittance of the glass-ceramic in the visible spectral range. They usually appear as impurities in the raw materials. These components are preferably included in the glass-ceramic in an amount of 0 to 0.5% by weight. Particularly preferably, they are included in the glass-ceramic in an amount of 0.001 - 0.4% by weight, 0.002 - 0.3% by weight, 0.004 - 0.2% by weight, 0.006 - 0.1% by weight, 0.008 - 0.08% by weight, or even 0.01 - 0.05% by weight.
[0083] In a preferred embodiment, the glass-ceramic contains 0 to 0.1% by weight of V2O5 or 0 to 0.5% by weight of MoO3 or 0 to 0.6% by weight of Nd2O3 or 0 to 0.4% by weight of Fe2O3 or 0 to 0.5% by weight of CoO or 0 to 0.5% by weight of Cr2O3 or 0 to 0.5% by weight of NiO or 0 to 0.5% by weight of CuO or 0 to 0.5% by weight of MnO or a combination of these components.
[0084] In addition to the coloring effect, these components can also have a positive impact on the glass quality. This is especially the case for components that absorb in the infrared spectral range in the glass melt. Due to the absorption of infrared light, the heat introduced into the melting tank by the heating device can be more effectively absorbed by the glass melt. This causes the temperature of the glass melt to rise under the same energy input. This has a positive impact on both the melting of raw materials that are difficult to melt and the reduction of bubbles during clarification. This is especially the case for the above amounts of Fe2O3, CoO and NiO.
[0085] In a further embodiment of the present invention, for a thickness of 4 mm, the glass-ceramic has a light transmittance of 80 - 90% or 81 - 89% or 82 - 88% or even 83 - 87%. For a thickness of 4 mm, the glass-ceramic having such a light transmittance preferably has a transmission chromaticity C* in the range of 0 - 6, preferably 1.5 - 5, particularly preferably 3.0 - 4.6.
[0086] Herein, "for a thickness of 4 mm" means that the corresponding property is either determined on a sample with a material thickness of 4 mm or determined for different material thicknesses and converted to a material thickness of 4 mm. For the transmittance data, the Lambert-Beer law can be used for conversion.
[0087] In accordance with the provisions of DIN 5033, the light transmittance is determined using standard light type D65 in the wavelength range of 380 - 780 nm. This value corresponds to the luminance Y in the CIExyY color space.
[0088] The chromaticity C* is determined from the L*a*b* color coordinates according to the following formula:
[0089]
[0090] The color coordinates a* and b* are determined from the transmission spectrum of the glass-ceramic in a known manner using standard light of standard light type D65.
[0091] The glass-ceramic having a light transmittance of 80 - 90% for a thickness of 4 mm is particularly suitable for use as a fireplace viewing window or a cooking plate. In a fireplace, such a transmittance makes the flame particularly clearly visible. For example, in a cooking appliance, such a transmittance makes a light-emitting display with a relatively low luminous density (such as an LCD or OLED display) particularly clearly visible.
[0092] A chromaticity C* of 0 - 6 causes only a very slight change in the color of light when passing through the glass-ceramic. For example, this enables the glass-ceramic to have a white coating, and when observing through the glass-ceramic, the white coating can still produce a white impression. For example, when used as a cooking surface or a fireplace viewing window, this is particularly important. The glass-ceramic in these applications usually has a thickness of 4 mm. The light reflected by the rear coating thus travels an optical path of 8 mm, making the color shift caused by the inherent color of the glass-ceramic have a greater effect compared to a shorter path. Therefore, a relatively low chromaticity is particularly advantageous for a cooking surface or a fireplace viewing window with a white coating on the rear side.
[0093] In a further embodiment of the present invention, the glass-ceramic having a light transmittance of 80 - 90% or a corresponding preferred range and having a chromaticity C* of 2 - 6 or a corresponding preferred range, in addition to the composition according to the present invention, further contains one or more of the following components (in wt%):
[0094] Nd2O3 is 0.005 - 0.1, preferably 0.01 - 0.08, particularly preferably 0.03 - 0.065,
[0095] Fe2O3 is 0 - 0.02, preferably 0.0025 - 0.018, particularly preferably 0.005 - 0.016,
[0096] V2O5 is 0 - 0.0015, preferably 0 - 0.001, particularly preferably 0 - 0.0005,
[0097] Cr2O3 is 0 - 0.001, preferably 0 - 0.0005, particularly preferably 0 - 0.0003,
[0098] MoO3 is 0 - 0.001, preferably 0 - 0.0008, particularly preferably 0 - 0.0006,
[0099] CoO is 0 - 0.001, preferably 0 - 0.0005, particularly preferably 0 - 0.0001,
[0100] NiO is 0 - 0.001, preferably 0 - 0.0005, particularly preferably 0 - 0.0001,
[0101] CuO is 0 - 0.001, preferably 0 - 0.0007, particularly preferably 0 - 0.0002,
[0102] MnO is 0 - 0.02, preferably 0 - 0.01, particularly preferably 0 - 0.006,
[0103] TiO2 is 1.6 - 2.5, preferably 2.0 - 2.4, particularly preferably 2.1 - 2.3,
[0104] ZrO2 is 0 - 2.2 or 0.1 - 2.0 or 0.2 - 1.8, or even 0.3 - 1.6,
[0105] SnO2 is 0.05 - 0.2, preferably 0.08 - 0.18, particularly preferably 0.1 - 0.15.
[0106] In a particularly preferred further embodiment, the glass - ceramic contains all these components in these amounts. If these components are included in the glass - ceramic in the amounts mentioned herein, then further preferably, the sum of Fe2O3 + V2O5 + Cr2O3 is 0 - 0.0225 wt%, preferably 0.0005 - 0.0175 wt%, particularly preferably 0.0010 - 0.0170 wt%.
[0107] These components, either alone or in combination with each other, affect the light transmittance and chromaticity of the glass-ceramics. If the above amounts are adhered to, fine adjustment of the light transmittance and chromaticity can be carried out within the above ranges.
[0108] The following table contains three refinements of the glass-ceramics according to the invention, based on oxides and in % by weight:
[0109]
[0110]
[0111] The uses of the glass-ceramics according to the invention are as a cooking surface, a fireplace viewing window, a grill or frying surface, a lid for a combustion element in a gas grill, an oven viewing window (especially a viewing window of a pyrolysis furnace), a workbench or tabletop in a kitchen or laboratory, a lid for a lighting device, a refractory glass and a safety glass, optionally for a laminated composite material, a carrier plate or an oven lining in heat treatment or a rear cover of a mobile electronic device.
[0112] The glass-ceramics according to the invention can in particular be used as a cooking surface. The cooking surface can here be provided in whole or in part on the top and / or bottom with a decorative or functional coating. A touch sensor for operating the cooking surface can also be provided on the bottom surface. This can for example be a printed, adhered or pressed capacitive sensor.
[0113] Furthermore, the glass-ceramics can also be present in the form of a three-dimensionally shaped plate. This means that the plate can be angled or curved, or for example contain areas shaped in the form of a wok. A cutout for operating a gas burner is also possible, for example. Detailed Description
[0114] The present invention will be further described below with reference to the embodiments.
[0115] The crystallizable green glass of the embodiment is melted from batch raw materials commonly used in the glass industry at a temperature of 1680 °C for 4 hours. This choice can meet the requirements for economical raw materials and the requirements for undesired impurities with low impurity content. After melting the batch in a crucible made of sintered quartz glass, the melt is poured into a Pt / Rh crucible with an inner crucible made of quartz glass and homogenized by stirring at a temperature of 1600 °C for 90 minutes. After homogenization, the glass is clarified at 1640 °C for 3 hours. Subsequently, blocks with dimensions of approximately 120×140×30 mm 3 are cast and cooling is started in a cooling furnace from 640 - 670 °C to room temperature at 30 K / h (depending on the viscosity of the glass) to reduce stress. The cast blocks are divided into the dimensions required for research and ceramization.
[0116] The ceramization of the samples in the green glassy state is carried out in a continuous furnace by a ceramization method in the following steps:
[0117] a) Heating from room temperature to 740 °C at a heating rate of 30 K / min,
[0118] b) Holding at 740 °C for 3 minutes and 20 seconds,
[0119] c) Increasing the temperature from 740 °C to 810 °C at a heating rate of 28 K / min,
[0120] d) Holding at 810 °C for 9 minutes and 20 seconds,
[0121] e) Increasing the temperature from 810 °C to 930 °C at a heating rate of 21 K / min,
[0122] f) Holding at 930 °C for 6 minutes,
[0123] g) Cooling to room temperature at a cooling rate of 15 K / min.
[0124] The following table contains the compositions and material properties of the examples according to the invention.
[0125] In the case of a heating rate of 2 K / min, the coefficient of thermal expansion CTE of the rod-shaped samples is determined dynamically with the aid of a push-rod dilatometer.
[0126] To measure the upper devitrification temperature (OEG), the green glass is melted in a Pt / Rh10 crucible. Then the crucible is held at different temperatures within the processing temperature range for 5 hours. The highest temperature at which the first crystals appear at the contact surface of the glass melt with the crucible wall determines the OEG.
[0127] According to the DIN ISO 7884-2 standard, a stirring viscometer is used to determine the processing point (T4) of the green glass.
[0128] When the green glass is transformed into glass-ceramics, the density increases because the density of the crystalline phase is higher than that of the amorphous glass. The shrinkage rate represents the linear change in length when the green glass is transformed into glass-ceramics. It is calculated from the density of the green glass and the density of the glass-ceramics:
[0129]
[0130] Tg represents the transformation temperature of the green glass, also known as the glass transition temperature. It is determined by the dilatometric method.
[0131] In accordance with the provisions of DIN 5033, the light transmittance is determined using light of the standard light type D65 in the wavelength range of 380 - 780 nm. This value corresponds to the luminance Y in the CIExyY color space. This value is a measure of the human eye's brightness perception.
[0132] According to the xy color coordinates in the CIExyY color space, the distance d to the color coordinates (0.3127 / 0.3290) of the standard light of standard light type D65 is determined as follows:
[0133]
[0134] The transmission spectrum is determined according to ISO 15368:2021. Table 2 exemplarily includes the spectral transmittances "T@..." for wavelengths 470 nm, 600 nm, 630 nm, 700 nm, 950 nm, and 1600 nm.
[0135] According to the provisions of CIE 1932, the color coordinates in the CIExyY color space and the Lab color space are determined in transmission with an 8° observer angle and using the light of standard light source D65.
[0136] All transmission measurements are performed on samples with a thickness of 4 mm and smooth surfaces on both sides.
[0137] Rietveld analysis is used to determine the volume fraction "XRD fraction HQMK" or "KMK" and the grain size of the crystalline phase "XRD grain size HQMK" or "KMK" from the X-ray diffraction spectrum.
[0138] Example 1 2 3 4 <![CDATA[Li2O]]> 2.210 2.03 2.44 2.61 <![CDATA[Na2O]]> 0.172 0.31 0.32 0.29 <![CDATA[K2O]]> 0.231 0.21 0.34 0.32 MgO 1.590 1.66 1.83 1.64 CaO 0.990 0.72 0.56 0.52 SrO 0.014 0.01 0.01 0.01 BaO 1.510 1.48 1.58 1.54 ZnO 3.100 4.05 3.49 3.17 <![CDATA[Al2O3]]> 18.589 17.46 19.33 19.29 <![CDATA[SiO2]]> 66.498 66.98 64.98 65.50 <![CDATA[TiO2]]> 3.220 3.18 3.19 3.18 <![CDATA[ZrO2]]> 1.396 1.38 1.40 1.38 <![CDATA[SnO2]]> 0.260 0.28 0.28 0.28 <![CDATA[Fe2O3]]> 0.117 0.121 0.116 0.120 <![CDATA[V2O5]]> 0.040 0.016 0.017 0.017 <![CDATA[Cr2O3]]> 0.004 0.004 0.005 0.004 <![CDATA[MnO2]]> 0.015 0.014 0.016 0.017 <![CDATA[P2O5]]> 0.063 0.06 0.07 0.07
[0139] Table 1: Composition of an example according to the invention
[0140] Example 1 2 3 4 T4[℃] 1314 OEG [℃] 1275 Density of glass [g / cm^3] 2.501 CTE of glass-ceramic [ppm / K] 1.01 1.63 1.30 0.93 Shrinkage rate [%] 1.34 1.94 1.28 1.17 <![CDATA[Density Glass-ceramics [g / cm 3 > 2.604 2.6616 2.6126 2.5944 XRD fraction HQMK 64 63 64 66 XRD grain size HQMK 73 46 82 78 XRD fraction KMK 0 0 0 0 Transmittance at 4 mm x (CIE) 0.686 0.544 0.541 0.568 y (CIE) 0.313 0.379 0.365 0.365 Y(CIE) / tvis [%] 0.029 1.094 0.814 0.570 d = sqrt((x - 0.3127)^2+(y - 0.3290)^2) 0.373 0.2368 0.2313 0.2577 T@470nm 0.0% 0.2% 0.2% 0.1% T@600nm 0.0% 1.8% 1.3% 0.9% T@630nm 0.1% 3.4% 2.6% 2.0% T@700nm 2.0% 11.1% 10.0% 8.9% T@950nm 53.7% 50.3% 56.7% 59.1% T@1600nm 69.2% 67.7% 69.5% 69.0%
[0141] Table 2: Material properties of an example according to the invention.
Claims
1. A lithium aluminosilicate glass-ceramic, having a thermal expansion coefficient in the range of -0.5 to 1.9 ppm / K from 20 °C to 700 °C, and comprising, on an oxide basis and in % by weight, a composition:
2. The lithium aluminosilicate glass-ceramic according to claim 1, characterized in that, The lithium aluminosilicate glass-ceramic contains 2.1 - 2.9% by weight, or 2.2 - 2.8% by weight, or 2.3 - 2.7% by weight, or even 2.4 - 2.6% by weight of Li2O.
3. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains 1.6 - 3.6% by weight, 1.7 - 3.3% by weight, 1.8 - 3.0% by weight, 1.9 - 2.6% by weight, or even 2.0 - 2.3% by weight of MgO.
4. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains 3.1 - 5.6% by weight, 3.2 - 5.3% by weight, 3.3 - 5.0% by weight, 3.4 - 4.7% by weight, or even 3.5 - 4.3% by weight of ZnO.
5. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains 0 - 0.5% by weight, or 0.05 - 0.4% by weight, or even 0.1 - 0.3% by weight of Na2O.
6. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains 0 - 0.5% by weight, or 0.05 - 0.4% by weight, or even 0.1 - 0.3% by weight of K2O.
7. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The amount of Na2O + K2O is at least 0.2% by weight and at most 1% by weight, preferably at least 0.3% by weight, 0.4% by weight, or even 0.5% by weight, and at most 1.0% by weight, 0.9% by weight, 0.8% by weight, 0.7% by weight, or even 0.6% by weight.
8. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The ratio K2O / Na2O, in % by weight, is in the range of 0.1 - 2, preferably 0.5 - 1.5, particularly preferably 0.7 - 1.3, or in the range of 0.1 - <1, preferably 0.2 - 0.9, particularly preferably 0.3 - 0.8, or in the range of 1 - 2, preferably 1.1 - 1.9, particularly preferably 1.2 - 1.
8.
9. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains 0.1 - <1.0% by weight of SnO2, preferably 0.15 - 0.8% by weight, particularly preferably 0.2 - 0.6% by weight of SnO2.
10. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains less than 0.1% by weight of As2O3 and less than 0.1% by weight of Sb2O3.
11. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains 1.0 - 4.0% by weight, or 1.2 - 3.6% by weight, or 1.4 - 3.3% by weight, or even 1.6 - 3.0% by weight of BaO.
12. The lithium aluminosilicate glass-ceramic according to claim 1, wherein The lithium aluminosilicate glass-ceramic contains 1.0 - 5.0% by weight, preferably 2 - 4.5% by weight, particularly preferably >2.5 - 4.0% by weight of TiO2.
13. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains 1.0 - 4.0% by weight, preferably >1.3 - 3.9% by weight, particularly preferably >1.7 - 3.8% by weight of ZrO2.
14. The lithium aluminosilicate glass-ceramic according to any one of the preceding claims, characterized in that, The lithium aluminosilicate glass-ceramic contains from 0 to 0.1% by weight of V2O5 or from 0 to 0.5% by weight of MoO3 or from 0 to 0.6% by weight of Nd2O3 or from 0 to 0.4% by weight of Fe2O3 or from 0 to 0.5% by weight of CoO or from 0 to 0.5% by weight of Cr2O3 or from 0 to 0.5% by weight of NiO or from 0 to 0.5% by weight of CuO or from 0 to 0.5% by weight of MnO or a combination of these components.
15. Use of the glass-ceramic according to any one of the preceding claims, as: a cooking surface; a fireplace viewing window; a grill or frying surface; a lid for a combustion element in a gas grill; an oven viewing window, in particular a viewing window of a pyrolysis oven; a workbench or tabletop in a kitchen or laboratory; a lid for a lighting device; a refractory glass and a safety glass; an optional laminated composite material; a carrier plate or an oven lining in heat treatment or a rear cover of a mobile electronic device.
Citation Information
Patent Citations
Transparent, colored cooking surface with improved color display capability and method for manufacturing such a cooking surface
DE102008050263B4
Transparent, colored cooking surface and method for indicating an operating state of such a surface
DE102009013127B4
Glass ceramic with reduced lithium content
EP3502069A1
Partially crystallised glass plate
US20170050880A1
Beta-quartz glass-ceramics with high zinc content
US20200140322A1